Function of epithiospecifier protein gene from broccoli - YUAN Gao-feng; WANG Qiao-mei (浙江大学学报. 农业与生命科学版)
Glucosinolates are a group of sulfur- and nitrogen-containing secondary metabolites that occur in crops belonging to the family of Brassicaceae. Glucosinolates are chemically stable until they become in contact with the enzyme myrosinase. Upon tissue damage, glucosinolates are released from plant vacuoles and rapidly hydrolyzed by myrosinase to glucose and other unstable thiohydroximate-O-sulfonate intermediates, which, as dictated by chemical conditions, spontaneously rearrange to isothiocyanates, thiocyanates, or nitriles. The chemical nature of the hydrolysis products from the glucosinolate-myrosinase system depends on the presence or absence of supplementary proteins, such as epithiospecifier proteins (ESPs). ESPs are specifically involved in the glucosinolate degradation catalyzed by myrosinase. ESPs have been purified and identified in Crambe abyssinica, Arabidopsis thaliana, Brassica napus and Brassica oleracea that appear responsible for the formation of epithionitriles. However, the function of ESP in the regulation of glucosinolate hydrolysis and its physiological role in Brassica vegetables remain unclear.The objective of the present study was to analyze the function of BoESP and investigate the regulation mechanism of ES P in glucosinolate hydrolysis of Brassica vegetables.Total RNA was extracted from broccoli (Brassica oleracea L. ssp. italica) used as the template to amplify the full length of cDNA of broccoli ESP gene (BoESP) by RT-PCR, and the gene fragment was subsequently cloned into pMDTM20-T vector. BoESP gene was digested completely from pMDTM20-T-BoESP vector by Kpn Ⅰ and BamH Ⅰ, and the gene fragment was cloned into plant expression vector pCambia2301. The overexpression construct of BoESP was then introduced into the model plant A. thaliana by Agrobacterium tume faciens-mediated genetic transformation. The seeds of T0 plants were sown on medium containing 50 mg/L kanamycin and the resistant plants were verified by PCR amplification to be transgenic A. thaliana. The transgenic T1 seeds were sown and seedlings were harvested after 3 weeks. The hydrolysis products of glucosinolate in transgenic T1 seedlings were analyzed by gas chromatograph with flame ionization detector and the compositions of hydrolysis products in vivo in the transgenic plants were evaluated.The results from the electrophoresis of PCR-amplified products confirmed that the cDNA of BoESP was successfully cloned. The results of double restriction enzyme digestion of BoESP CaMV35S by Kpn Ⅰ and BamH Ⅰ and PCR detection of BoESP CaMV35S in A. tume faciens EHA105 showed the successful construction of plant overexpression vector BoESP CaMV35S. The transformation with the BoESP CaMV35S construct altered the constituents of glucosinolate hydrolysis products in A. thaliana. The content of 4-methoxy-indole-3-acetonitrile in A. thaliana with BoESP overexpression was significantly increased by 3.49%, whereas that of 1-isothiocyanato-4-methanesulfinyl-butane in A. thaliana with BoESP overexpression was significantly decreased by 17.63%, compared with the wild-type plants.As a result, it is provided the direct evidence for the regulatory role of BoESP in glucosinolate metabolism. The research on the function of ESP in the regulation of glucosinolates hydrolysis can provide unique tools in agricultural crops as a strategy to improve their insect and pathogen resistance as well as nutrition value. Our findings are of great theoretical significance and potential in crop improvement.